Issues of Indian Security in Indo-Russian Strategic Relations: Examining the Impact of the USSR's Collapse on Indo-Russian Relations (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The impact of Indo-Russian relations on the domestic and foreign policies of India from the 1960s is difficult to underestimate. The USSR was instrumental in helping independent India industrialize, develop its scientific potential, and defend its territorial integrity. The Indo-Russian relationship developed a level of trust between two independent countries that was unprecedented in international affairs. The collapse of the USSR negatively affected the bilateral relations, though the political leadership in both countries succeeded in containing the impact. Today the two countries need to find new ways to reignite their ties in a rapidly changing international system.